Identificando dificuldades e benefícios do uso do PSP apoiado por ferramentas de 3ª. geração - Montebelo, Renan Polo (Universidade Federal de São Carlos, 2008)
Background: The Personal Software ProcessTM (PSP) is a methodology that can be used by software developers to improve the predictability, the productivity and the quality of their personal work. However, the great number of activities and metrics involved in the PSP makes its application very laborious and difficult. Several PSP supporting tools have been proposed in order to make its application more feasible, and such tools evolved as more experiments were conducted with the PSP. There are now three generations of PSP supporting tools, whereas third generation supporting tools are characterized by being able to collect and analyze Software Engineering metrics automatically and unobtrusively. Objective: This study s objective is to determine the difficulties and benefits of using third generation tools to support the PSP application. Method: The GQM paradigm was used to set up two Case Studies, one being in the academic environment with undergraduate students and another in a small software development company. Both case studies featured the PSP application supported by third generation tools. Results: Results show that third generation supporting tools have some advantages over previous generations tools, especially in the coding phase. However, third generation tools have limited PSP activities support and introduce new adoption problems. Conclusion: For a successful long-term PSP application, it is necessary that the supporting tools are completely adapted and integrated in the developers work environment, with both second and third generations tools characteristics.
Keywords: Engenharia de software; PSP; SW-CMM - Modelo de capacidade de processo; Qualidade de software; Engenharia de software - experimentação; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::ENGENHARIA DE SOFTWARE